Kristonomi sebagai Hukum yang Hidup: Partisipasi, Ketaatan, dan Kebebasan - Sitorus, Yohannes Ali Sandro (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article discussed the concept of Christonomy as a constructive proposal based on the reading of Ephesians 4:17-32. Such a concept answered the problem of the tension between obedience and freedom of the new human (new self) as opposed to the old human (old self). Biblical, theological, and ethical approaches were employed, with special attention to the theology of participation. This article demonstrates that new humans are invited to confess the personhood Christ as the supreme ethical norm called “the Living Law” in response to the diversity of ethical norms. The Christonomic idea of Christ as the Living Law is also a new proposal that reconciles the classical problem of theonomy, autonomy, and heteronomy.AbstrakArtikel ini membahas konsep Kristonomi sebagai sebuah proposal konstruktif berdasarkan pembacaan atas Efesus 4:17-32. Konsep ini menjawab persoalan seputar ketegangan antara ketaatan dan kebebasan manusia baru yang berlawanan dengan manusia lama. Pendekatan-pendekatan biblis, teologis, dan etis dipergunakan, dengan perhatian khusus pada teologi partisipasi. Artikel ini memperlihatkan bahwa, dalam merespons kemajemukan norma etis, manusia baru diundang untuk mengakui pribadi Kristus sebagai norma etis terunggul, yaitu sebagai “Hukum yang Hidup”. Gagasan Kristonomis mengenai Kristus sebagai Hukum yang Hidup ini juga menjadi sebuah usulan baru yang memperdamaikan masalah klasik mengenai teonomi, otonomi, dan heteronomi.